Global research trends and hotspots for leukocyte cell-derived chemotaxin-2 from the past to 2023: a combined bibliometric review - Liu, Wei; Wang, Qin; Yeerlan, Jianishaya; Yan, Yirui; Xu, Luke; Jia, Cui; Liu, Xinlian; Zhang, Lushun (Frontiers in Immunology, 2024)
Leukocyte cell-derived chemotaxin-2 (LECT2) is an an important cytokine synthesized by liver. Significant research interest is stimulated by its crucial involvement in inflammatory response, immune regulation, disease occurrence and development. However, bibliometric study on LECT2 is lacking. In order to comprehend the function and operation of LECT2 in human illnesses, we examined pertinent studies on LECT2 investigation in the Web of Science database, followed by utilizing CiteSpace, VOSview, and Scimago Graphica for assessing the yearly quantity of papers, countries/regions involved, establishments, authors, publications, citations, and key terms. Results indicated a fluctuating ascending trend in LECT2associated literature. "Angiogenesis", "ALECT2", "diagnosis", and "biliary atresia" are the current investigative frontiers. Our findings indicated that liver diseases (e.g. liver fibrosis and hepatic cell carcinoma), systemic inflammatory disease, and amyloidosis are the current research focus of LECT2. We hope to promote the scientific research of LECT2 and exploit its potential for clinical diagnosis and treatment of related diseases through a comprehensive bibliometric review.